Latent profiles of emotional intelligence: Russian and Chinese samples - Tatiana V. Kornilova; Qiuqi Zhou; Victoria A. Savelieva (Теоретическая и экспериментальная психология)
Background. Research on emotional intelligence (EI) has a long history, however, most of it has been focused on understanding EI as an ability, and the existing studies of latent profiles of EI as a trait have been conducted mainly on European samples. Objectives. The study had its purpose to identify commonalities and differences in emotional intelligence between Russian and Chinese adult people. Study Participants. A total of 698 people: 1) 312 Chinese participants aged 18 to 55 years (Mage = 29.16; σ = 11.34), of which 120 were men (32.9%); 2) 386 Russian participants aged 18 to 60 years (Mage = 24.96; σ = 8.0), of which 126 were men (38.5%). Methods. The study implemented the Trait Emotional Intelligence Questionnaire (TEIQue) adapted in Russian by Kornilova (2023) which includes four scales: Well-Being, Sociality, Emotionality, and Self-Control. Processing the data obtained included correlation analysis, the latent class analysis, comparison method, and cross-cultural analysis. AIC, BIC, aBIC, aLRT were used. Results. In general, the latent class analysis demonstrated the possibility of identifying two classes of individuals in both the Russian and Chinese samples — differing in all 4 EI components in the Russian sample and in 3 components — in the Chinese sample. The identified groups are characterized by different combinations of indicators of well-being, negative emotionality, and self-control. A cross-cultural difference between the two samples was found, which manifests itself in a discrepancy between Russian classes in “sociality” (high or low with higher or lower “self-control”), which is practically absent in the Chinese sample. Conclusions. Latent structures of EI traits in a cross-cultural comparison of Russian and Chinese samples show more similarities than differences; the latter are manifested in the presence vs absence of discrepancies between the levels of sociality among the classes identified in both samples. Latent class analysis indicates no gender differences in the structure of emotional intelligence in the Russian sample, while revealing some differences in “sociality” in the Chinese sample.